Utilization of Tofu Dregs Waste as a Value Added Product in Pondokrejo Village, Jember - Muhdar Muhdar; Cindy Prasetia Sari; Berliana Maharis Arrishala; Gilang Maulana Bilhaq (Trescode Green Organization, 2024)
Tofu dregs are easily perishable waste, so they cannot be stored for a long time. The people of Pondokrejo Village so far have not innovated regarding MSME products, especially production waste. Therefore, the use of tofu dregs aims to make processed food in the form of products that have economic value so that they can improve the economy of Pondokrejo Village. In this study, data collection was carried out using qualitative research methods, specifically using interview and survey techniques. In the early stages, the author conducted interviews with Pondokrejo Village officials to find out about MSMEs in Pondokrejo Village and conducted an FGD (Focus Group Discussion) by explaining about tofu waste to increase selling value and collect suggestions and input regarding product innovation. New knowledge and perspectives regarding tofu waste which is processed into innovative stick products were given to tofu entrepreneurs, PKK mothers, and Posyandu cadres. Apart from that, the importance of e-commerce accounts, where marketing through digital marketing is a very important forum for disseminating the marketing goals of a product. Based on this research, it can be concluded that tofu waste can be reprocessed into value-added products. The waste was obtained from the production of tofu in Pondokrejo Village, which was originally used as livestock feed for the residents and then reprocessed into an innovative snack product, namely